1999
DOI: 10.1046/j.1365-2982.1999.00167.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between blood flow and motility in normal and inflamed ileum

Abstract: The alterations in local and superior mesenteric blood flow during ileal inflammation and their correlations with motility in the normal and the inflamed ileum were investigated in the conscious state. Ileal inflammation decreased the local mesenteric blood flow but had no significant effect on the superior mesenteric blood flow. A significant reduction or an increase in local mesenteric blood flow in the normal or the inflamed ileum had no effect on local contractile activity. The vascular reactivity to vaso-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…provided less conclusive results. In the latter study, increased motility in response to Ang II administration was detected in only three of five normal dogs and identical results were obtained in dogs with an artificially induced Crohn’s‐like inflammation (Cowles et al. 1999).…”
Section: Discussionsupporting
confidence: 71%
“…provided less conclusive results. In the latter study, increased motility in response to Ang II administration was detected in only three of five normal dogs and identical results were obtained in dogs with an artificially induced Crohn’s‐like inflammation (Cowles et al. 1999).…”
Section: Discussionsupporting
confidence: 71%
“…98 In addition, the increase in blood flow induced by the b adrenergic agonist isoproterenol was markedly lower in inflamed ileum. 99 These studies in animal models of intestinal inflammation support the concept of a b to a adrenergic shift. The functional consequences are further corroborated by repulsion of sympathetic nerve fibres ( fig 5B).…”
Section: Link Between Leucocyte Infiltration Innervation and Motilimentioning
confidence: 68%
“…Cowles et al. () have shown that transient reduction of blood flow does not interfere with motility of the ileum in dogs. The effects of transient reduced blood flow in the duodenum of dogs remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed that the addition of MK-467 also attenuates the DEX-induced reduction of blood flow in the small intestine. Cowles et al (1999) have shown that transient reduction of blood flow does not interfere with motility of the ileum in dogs. The effects of transient reduced blood flow in the duodenum of dogs remain to be elucidated.…”
Section: Figurementioning
confidence: 96%